Network analysis of shariah-compliant stocks on Bursa Malaysia by using minimum spanning tree (MST) - Mahamood, Fatin Nur Amirah; Bahaludin, Hafizah; Abdullah, Mimi Hafizah (AIP Publishing, 2019)
In this study, a financial network of stocks traded in Bursa Malaysia was constructed using a minimum spanning tree (MST) method. The network constructed focuses on the companies that are listed in the shariah-compliant measures degree, betweenness and closeness centrality were used to determine the most influential stock. The financial network helps market participants by providing an overview of correlations of stocks and identifying the stocks that have major roles in the market as well as presents as a platform for the design of investment tactics.